Accelerating uptake of new Medicare payment models: Medicare officials want to expand alternative payment models to help slow the growth of healthcare costs and preserve the solvency of the program, currently anticipated to go bankrupt by 2030 - Weeks, Bill; Gregg, Judd; Fisher, Elliott S.; Weinstein, James (Healthcare Financial Management, 2015)
Abstract